Estudio de la población microbiana en un sistema de biorremediación in situ de un suelo impactado con hidrocarburos de petróleo. - Ledezma Villanueva, Alejandro (2016)
Bioremediation involves various techniques in which different biotic factors are applied in terrestrial and aquatic habitats that were contaminated with recalcitrant chemicals. Any technique tends to achieve the decrease of the pollutants following the regulations of each country and with this avoiding the loss of large amounts of soil as the most common solution is to confine soil or water. Bioremediation reduces high costs generated by confinement because it involves training, transportation and extensive use of heavy machinery thus resulting in a not very affordable way for the economy and in most cases the site is left behind in a state of environmental liability for an indefinite period until the authority establish an agreement for a treatment. The discovery of bioremediation was based on the observation and recording of contaminated habitats. For example we can cite the how plants filter in their specialized vascular system contaminants which make contact with well water. Another activity that shows the nature of soils are contaminated land sites that have been integrated over time (more than a hundred years) by a process called natural attenuation where the natural environment factors such as wind, relative humidity, lightning and temperature are presented daily letting the soil to reduce its pollutants by 25% of the original volume and eventually to its initial state. These findings were reproduced in the laboratory over the world in order to mimic the natural attenuation process. Based on the reasons explained above, the present study explores the analysis of variation in the population of a bacterial consortium called for practical purposes as CMIC 4 which was previously isolated from a highly contaminated soil (35,000 ppm) with Aromatic Hydrocarbons (PAH) for more than 30 years. In our laboratory (LMYF) a pyrosequencing in the 16s ribosomal DNA extracted from the bacterial consortium took place integrating data in order to design specific oligonucleotides of the main genus and therefore create a system to monitor presence and growth during a In Situ bioremediation process. The technique was used to visualize their variability in a bio stimulation process on a different PAH polluted soil. The process of field testing took place at the landfill site of a private company dedicated to the handling, collection and disposal of hazardous chemicals. The soil inoculated with the consortium under temperature uncontrolled reached pollutant degradation in just 30 days. Following the treatment, the resulting soil had a toxicity test were the earthworm Eisenia fetida was used as a bio indicator, having satisfactory results since it did not die and increased its weight.